Keefektifitasan Effleurage Massage Ketika Fase 1 Aktif - Suprida Suprida; Rochmah KM; Iyang Shensi Niarty (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2021)
Background: About 90% of mothers are always accompanied by pain while pain in labor is a common thing. Great pain in the labor process causes the mother to experience psychological disorders, 87% post-partum blues that occur from 2 weeks postpartum to 1 year, 10% Depressi, and 3% with Psychosis.The Aim: To determine the effect of effleurage massage on the decrease in intensity of pain during phase I active in BPM Husniyati and BPM Yuhana Palembang in 2018.Method: This research uses pre test experiment method with One Group Pretest Posttest design. The sampling was taken by purposive sampling technique. The sample was 30 respondents.The Results: Based on the univariate analysis of labor pain intensity before effleurage massage was mostly on the 7-9 scale (severe pain) as much as 16 respondents (53.3%) while the intensity of labor pain after effleurage massage was mostly on 1-3 (mild pain) as many as 14 respondents (46.6%). From the result of bivariate test using Wilcoxon test, it got significant value (p value = 0,000), so p <0,05.Conclusion: There is influence of effleurage massage on the decrease in the intensity of pain during phase I active in BPM Husniyati and BPM Yuhana Palembang in 2018. Therefore, it is expected that health workers in particular to apply effleurage massage as a method to reduce the intensity of pain in maternal delivery.